2009
DOI: 10.1128/jb.00995-09
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Response to Spermine, a Component of the Intramacrophage Environment, Reveals Regulation of Francisella Gene Expression through Insertion Sequence Elements

Abstract: Tularemia is caused by the category A biodefense agent Francisella tularensis. This bacterium is associated with diverse environments and a plethora of arthropod and mammalian hosts. How F. tularensis adapts to these different conditions, particularly the eukaryotic intracellular environment in which it replicates, is poorly understood. Here, we demonstrate that the polyamines spermine and spermidine are environmental signals that alter bacterial stimulation of host cells. Genomewide analysis showed that F. tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 42 publications
3
60
0
Order By: Relevance
“…Buffy coats from blood donations (Central Blood Bank, Pittsburgh, PA) served as the source of human monocytes that were differentiated into macrophages by in vitro culture as has been detailed previously (9,10,27,29,50). For in vitro infections, primary human macrophages were washed and resuspended in Dulbecco's modified Eagle's medium (DMEM) supplemented with 1% human serum AB (complement replete; GemCell Gemini Bio-Products), 25 mM HEPES, and 1% GlutaMAX and then plated onto Primaria-coated 96-well culture dishes (Becton, Dickinson and Company) at a density of 5.0 ϫ 10 4 cells per well as we have described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…Buffy coats from blood donations (Central Blood Bank, Pittsburgh, PA) served as the source of human monocytes that were differentiated into macrophages by in vitro culture as has been detailed previously (9,10,27,29,50). For in vitro infections, primary human macrophages were washed and resuspended in Dulbecco's modified Eagle's medium (DMEM) supplemented with 1% human serum AB (complement replete; GemCell Gemini Bio-Products), 25 mM HEPES, and 1% GlutaMAX and then plated onto Primaria-coated 96-well culture dishes (Becton, Dickinson and Company) at a density of 5.0 ϫ 10 4 cells per well as we have described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the importance of central metabolism (e.g., glycolysis) has also been shown to play a role during infection (149). Additionally, there is evidence that nutritional status may play a role in allowing Francisella to sense the host phagosome compared to being in the host cytosol (40) and to induce expression of virulence genes, including those required for phagosomal escape (40,67,191). Mutants that are unable to recognize particular metabolites, such as polyamines present in the host cytosol, are significantly attenuated and unable to alter temporal expression of virulence factors (191).…”
Section: Nutritional Defensesmentioning
confidence: 99%
“…Successful evasion of the host immune response may be partly due to an adaptation of F. tularensis to the intracellular environment (7,34). Loegering et al demonstrated that after replication within macrophages F. tularensis is less stimulatory in subsequent macrophage infections compared to F. tularensis cultured in bacterial growth media (34).…”
mentioning
confidence: 99%
“…However, the mechanism(s) enabling F. tularensis to sense and adapt to the host environment must be delineated. Among possible signals, polyamines, temperature, and amino acid concentration are known to be important environmental cues that alter bacterial virulence (7,26,28).…”
mentioning
confidence: 99%